Filipino ESL Learners’ Academic Efficacy, Thoughts and Achievements in the Blended Learning Modality - Ryan Kabigting (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2022)
This concurrent embedded strategy of mixed methods design described the ESL learners’ academic efficacy, thoughts and experience and achievement in the BL delivery modality. Fifty learners were purposively selected based on the set criteria. To determine the learners’ academic efficacy, the adapted survey questionnaire for academic self-efficacy scale (ASES) for junior high school learners developed by Mr. Angelo Reyes Dullas of Central Luzon State University (CLSU), Philippines was used, while a semi-structured questionnaire prompted the participants to describe their experiences during the blended learning modality. The collected quantitative data were analyzed and interpreted using the mean, frequency counts, and Pearson r while coding and theming for the qualitative data. The study found that the participants' mean grades were very satisfactory and outstanding during the first and second quarters, respectively. A calculated r-value of 0.78, strongly positively correlated, indicates that the learners’ academic efficacy goes with their performance. This means that the high the academic efficacy, the better the performance in English. The researcher has drawn at least five major themes based on the learners’ narrations. These are the self-directed learning is the new trend, internet connection at loss during OL, academic motivation makes learners go on, web-based educational sites as the source of information, and the student-teacher collaborative learning. This strengthens that BL is an opportunity for learners to learn amid the country’s health crisis.